A calm brain : unlocking your natural relaxation system - Devi, Gayatri (Dutton, 2012)
Shares advice on pursuing tranquility in the face of daily chaos, explaining how to harmonize the brain's rational and connected regions to achieve both calm and productivity at work, while parenting, and in interpersonal relationships.